Kemampuan Argumentasi Peserta Didik dalam Menyelesaikan Masalah Pembuktian Kongruensi Segitiga Ditinjau dari Perbedaan Gender - Nadia Ummi Sholihah; Lisanul Uswah Sadieda; Sutini Sutini (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2021)
This research aims to describe the argumentative abilities of male and female students to solve the triangular congruence proof problems. This research is a qualitative descriptive research. The subjects used in this research were 4 students of class X-MIPA1 at MAN Sumenep consisting of 2 male students and 2 female students. Sampling was done by using purposive sampling type quota sampling. Data collection techniques used written tests and interviews, then analyzed based on the indicators of Toulmin's argumentative ability consisting of claims, evidence, warrant, backing, qualifier, and rebuttal. The results showed that there were differences in the argumentation skills possessed by male and female students, as shown in the following data: (1) Male students were at level 1 in conveying their arguments with the fulfilled indicator being a claim. Male students tend to be more careless in solving problems, but they rely more on their verbal skills in answering. (2) Female students are able to reach level 3 in conveying their arguments with the indicators that are fulfilled are claim, evidence, and warrant. Female students tend to be thorough in working on questions and rely more on their symbolic abilities in answering.